Application of redefined J-integral range ΔJ for ultra-low cycle fatigue problems with large magnitude of elastic-plastic deformation - Shoda, Keigo; Arai, Koichiro; Nakamura, Sora; Okada, Hiroshi (Theoretical and applied fracture mechanics, 2023)
•Redefined J-integral range ΔJ was applied to ultra-low cycle fatigue problems.•Redefined J-integral range ΔJ is independent of size and shape of its integral domain.•Redefined J-integral range ΔJ by a domain integral can be applied to any structures.•Redefined J-integral range ΔJ can be applied to any finite strain problems.•Redefined J-integral range ΔJ does not pose any restrictions on constitutive models.•Subloading surface plasticity model reproduced load–displacement hystereses accurately. The redefined J-integral range ΔJ by a domain integral representation was applied to the ultra-low cycle fatigue problem of a 1 T compact tension (1TCT) specimen. The specimen was subject to large magnitude of cyclic deformation. The redefined J-integral range ΔJ is unconditionally independent of size and shape of its integral domain. The subloading surface plasticity model was adopted to appropriately reproduce the cyclic stress-strain behavior of the material. Finite element analyses on and evaluations of ΔJ were performed on the ultra-low cycle fatigue problem of a 1TCT specimen made of stainless steel SUS316. The outcomes of present study show the followings: (i) use of the redefined J-integral range ΔJ under the assumption of finite deformation theory, ductile crack propagations in ultra-low cycle fatigue problems can be characterized and (ii) deformation and load-displacement hystereses of the experiments can appropriately be reproduced by the use of the subloading surface plasticity model.